2015
DOI: 10.1103/physrevlett.114.157002
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Phase Transitions near Optimal Superconductivity inBaFe2(As1xP

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
57
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 38 publications
10
57
2
Order By: Relevance
“…Both the AF order and the structural transition disappear around the optimal doping level, indicating the presence of magnetic and/or nematic quantum critical points (QCPs). While there is increasing evidence that the magnetic QCP may not exist in many materials [12][13][14][15][16], the nematic QCP has attracted more and more interest since nematic quantum fluctuations may induce an attractive pairing interaction and thus enhance or even lead to superconductivity [17][18][19].So far, the evidence for the nematic QCP is rather limited. It is shown that the nematic order may go through a zero-temperature order-to-disorder quantum phase transition as shown by elastoresistance [3,9], elastic constants [4,5], and Raman scattering [7,8].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Both the AF order and the structural transition disappear around the optimal doping level, indicating the presence of magnetic and/or nematic quantum critical points (QCPs). While there is increasing evidence that the magnetic QCP may not exist in many materials [12][13][14][15][16], the nematic QCP has attracted more and more interest since nematic quantum fluctuations may induce an attractive pairing interaction and thus enhance or even lead to superconductivity [17][18][19].So far, the evidence for the nematic QCP is rather limited. It is shown that the nematic order may go through a zero-temperature order-to-disorder quantum phase transition as shown by elastoresistance [3,9], elastic constants [4,5], and Raman scattering [7,8].…”
mentioning
confidence: 98%
“…Both the AF order and the structural transition disappear around the optimal doping level, indicating the presence of magnetic and/or nematic quantum critical points (QCPs). While there is increasing evidence that the magnetic QCP may not exist in many materials [12][13][14][15][16], the nematic QCP has attracted more and more interest since nematic quantum fluctuations may induce an attractive pairing interaction and thus enhance or even lead to superconductivity [17][18][19].…”
mentioning
confidence: 99%
“…Compared with ARPES measurements, polarized INS measurements have much better energy and momentum resolution, and can directly probe the energy, wave vector, and temperature dependence of the spin excitation anisotropy and determine its relationship with T c , T N , T s , and nematic phase. For hole-doped Ba 1−x K x Fe 2 As 2 [35][36][37][38], electron-doped BaFe 2−x T M x As 2 (T M = Co, Ni) [39][40][41][42], and isovalent-doped BaFe 2 (As 1−x P x ) 2 [43][44][45] superconductors, unpolarized INS experiments found that superconductivity is coupled with the appearance of a low-energy collective spin excitation mode termed spin resonance that has superconducting order parameter-like temperature dependence below T c [46][47][48][49][50][51]. Although polarized INS experiments have conclusively established the presence of SOC induced lowenergy spin excitation anisotropy near the resonance mode in different families of iron-based superconductors [23][24][25][26][27][28][29][30][31][32][33][34], the spin excitation anisotropy persists in the paramagnetic tetragonal state, and becomes isotropic at temperatures well above T N and T s [25,26,[30][31][32].…”
mentioning
confidence: 99%
“…We chose BaFe 2 (As 0.7 P 0.3 ) 2 because the system has no AF order and structural distortion [45], and is believed to be near a magnetic [44] or a nematic quantum critical point [12]. Since the AF order in BaFe 2 (As 1−x P x ) 2 is gradually suppressed with increasing x similar to electron-and holedoped BaFe 2 As 2 [45], one would expect low-energy spin excitations in BaFe 2 (As 0.7 P 0.3 ) 2 to behave similarly to those of optimally doped BaFe 2−x T M x As 2 and (Ba,K)Fe 2 As 2 , and exhibit anisotropy at temperatures well above T c [25,26,32]. Surprisingly, we find that spin excitations are completely isotropic in spin space above T c for energies above 2 meV.…”
mentioning
confidence: 99%
“…6 (a), respectively. The first point to note is, that the calculations do not lead to a critical concentration x crit within the investigated regime of substitution, while on the experimental side one has x crit,exp (Ru-122) ≈ x crit,exp (P-122) ≈ 0.3 [60,61]. Isovalent doping should in general shift the Fermi level E F only marginally, leading to an unchanged nesting behavior.…”
Section: Isovalent Dopingmentioning
confidence: 99%